Analysis of the Benefits and Risks of Digital Payments on Cash Receipts at Hotels in Bali - Dewi, Ni Luh Gede Sri Mulya; Widawati, Ida Ayu Putri; Septiviari, Anak Agung Istri M. (Indonesian Journal of Banking and Financial Technology, 2024)
The use of digital payments in cash receipts at hotels in Bali has increased in the period 2021 to 2023. Cash receipts with digital payments are processed by accounts receivable and income audit. This study aims to determine the benefits and risks of cash receipts via digital payments at Hotel "X". This study uses qualitative descriptive data analysis techniques. The results of this study indicate that the benefits of digital payments provide convenience in the transaction process so that the transaction process can be carried out faster and provide security in the transaction process. The risks arising from digital payments are human error, system errors and double payments.